Label-free identification and chemical characterisation of single extracellular vesicles and lipoproteins by synchronous Rayleigh and Raman scattering. Issue 1 (1st January 2020) - Enciso-Martinez, Agustin; Van Der Pol, Edwin; Hau, Chi M.; Nieuwland, Rienk; Van Leeuwen, Ton G.; Terstappen, Leon W.M.M.; Otto, Cees
ABSTRACT: Extracellular vesicles (EVs) present in blood originate from cells of different origins such as red blood cells (RBCs), platelets and leukocytes. In patients with cancer, a small portion of EVs originate from tumour cells and their load is associated with poor clinical outcome. Identification of these tumour-derived extracellular vesicles (tdEVs) is difficult as they are outnumbered by EVs of different tissue of origin as well a large number of lipoproteins (LPs) that are in the same size range. In order to detect tdEVs from the abundant presence of other particles, single-particle techniques are necessary. Here, synchronous Rayleigh and Raman scattering is used for that purpose. This combination of light scattering techniques identifies optically trapped single particles based on Rayleigh scattering and distinguishes differences in chemical composition of particle populations based on Raman scattering. Here, we show that tdEVs can be distinguished from RBC EVs and LPs in a label-free manner and directly in suspension.